(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Genetic factors represent the major etiological contributor in Autism Spectrum Disorders (ASD) but several studies also support the involvement of environmental factors. This last hypothesis is reinforced by the evident increase in the prevalence of this disorder in the last decades. Thus, in our study, we aimed to identify the correlation between factors related to sociodemographic elements, to child and mother’s health and ASD in order to dress a best detailed profile of the patients. Methods: We conducted a case-control study including 64 Lebanese patients with ASD and 67 matched controls recruited from all the Lebanese districts. Our data has been analyzed by SPSS 23.0 and the statistical tests carried out were the Independent Sample t-test and the Chi-Square test. In addition, a multivariate logistic regression analysis has been carried out using variables that showed a p<0.05 in the bivariate analysis. Results: Our findings suggest that consanguinity (OR=4; 95% CI [1.3-12.04]), familial history of ASD (6.7 [1.1- 39.3]), stress during pregnancy (3.6 [1.5 8.2]) and fetal prematurity (6.3 [1.2-33.01]) were significantly associated with increased odds of ASD. However, our results have shown no association between siblings suffering from diseases such as mental retardation, child’s infections and ASD. Conclusion: This pilot study carried out in all the regions of Lebanon allowed us to shed the light on factors associated with ASD which might be preventable.